Management of fishery waste into liquid organic fertilizer in Hamadi Jayapura - Janviter Manalu; Kristina Haryati; Khristhoper Aris Arianto Manalu (University of Merdeka Malang, 2024)
Fishery waste is a problem that is very disturbing to the community because it causes strong odors, dirty views, and reduces water quality. Apart from having a negative impact, fishery waste still contains components needed for plant growth, such as nitrogen (N), phosphorus (P), and potassium (K). Therefore, it is essential to conduct community service activities for POKBAKER that involve the conversion of fishery waste into liquid organic fertilizer (POC). The aim of carrying out service activities is to provide understanding to participants through lectures and practical activities in making fertilizer from fisheries. The implementation methods expressed are three, namely pre-preparation, socialization activities (pre-test, lecture, post-test), and practical activities. The materials used in practical activities are fishery waste (gills and offal), EM4, molasses, and rice washing water. The results show that the percentage of answers to the six pre-test questions given ranges from 53-100 percent, while the percentage of the eight post-test questions given ranges from 93-100 percent. So, the conclusion is that this activity can increase the knowledge and understanding of the Fishery Waste Processing Group (POKBAPER) from 53 percent to 90 percent. Participants have the ability to plant liquid organic fertilizer from fishery waste.